The Expressive Creativity of Euphemism and Dysphemism - Miguel Casas Gómez (Lexis: Journal in English Lexicology)
Euphemism and dysphemism are two cognitive processes of conceptualisation, with countervalent effects (having the same base and resources but different aims and purposes), of a certain forbidden reality. The expressiveness immanent in these phenomena is so consubstantial that it explains not only its forbidden origin (the affective ambivalence of the taboo or the paradoxical description of its intrinsic essence), but also that sometimes the forbidden term does not exist, with the use of euphemistic/dysphemistic expressions that, given their connotative contents, go beyond what the corresponding forbidden terms would designate. It is precisely this expressive capacity of euphemistic and dysphemistic nature that shows that the dividing line between taboo and dysphemism is, on occasions, quite blurred, so that a taboo term is not readily available, and that the boundary between euphemism and dysphemism is not entirely clear. These conflicting emotions and antagonistic feelings facilitate the existence of dysphemistic euphemisms and euphemistic dysphemisms.Likewise, there are several mechanisms with an expressive base, corresponding to different linguistic levels, which make use of these phenomena in order to modulate, substitute, alter or modify a certain forbidden concept or reality. In this paper, we will stick to linguistic description with examples from a set of specific resources, which are especially significative for their expressiveness, and which favour the appearance of linguistic creations, sometimes through a lexical substitute and at other times through a morphological modification of a forbidden content, such as expressive designations, verbal exchanges or composition, as well as those other cases in which the attenuating nature of the euphemism is intensified with expressive enhancement in the creation of certain substitutions for reasons of puffery, which are so common in expressions which give additional social prestige to certain professions, trades and jobs.